History, mechanisms and clinical value of fibrillation analyses in muscle denervation and reinnervation by Single Fiber Electromyography and Dynamic Echomyography - Amber Pond; Andrea Marcante; Riccardo Zanato; Leonora Martino; Roberto Stramare; Vincenzo Vindigni; Sandra Zampieri; Christian Hofer; Helmut Kern; Stefano Masiero; Francesco Piccione (PAGEPress Publications, 2014)
This work reviews history, current clinical relevance and future of fibrillation, a functional marker of skeletal muscle denervated fibers. Fibrillations, i.e., spontaneous contraction, in denervated muscle were first described during the nineteenth century. It is known that alterations in membrane potential are responsible for the phenomenon and that they are related to changes in electrophysiological factors, cellular metabolism, cell turnover and gene expression. They are known to inhibit muscle atrophy to some degree and are used to diagnose neural injury and reinnervation that are occurring in patients. Electromyography (EMG) is useful in determining progress, prognosis and efficacy of therapeutic interventions and their eventual change. For patients with peripheral nerve injury, and thus without the option of volitional contractions, electrical muscle stimulation may be helpful in preserving the contractility and extensibility of denervated muscle tissue and in retarding/counteracting muscle atrophy. It is obvious from the paucity of recent literature that research in this area has declined over the years. This is likely a consequence of the decrease in funding available for research and the fact that the fibrillations do not appear to cause serious health issues. Nonetheless, further exploration of them as diagnostic tools in long-term denervation is merited, in particular if Single Fiber EMG (SFEMG) is combined with Dynamic Echomyography (DyEM), an Ultra Sound muscle approach we recently designed and developed to explore denervated and reinnervating muscles.